Bank Sampah Sebagai Alternatif Penyelesaian Sampah Yang Berkelanjutan Dan Peningkatan Ekonomi Di Desa Jatiwangsan Kecamatan Kemiri Kabupaten Purworejo - Yuli Widiyono; Arif Susanto; Ari Fajar Isbakhi; Nurholis Nurholis; Citra Maharani Ivoniya (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The Garbage Bank program carried out in Jatwansan village, Kemiri sub-district, Purworejo district, Central Java is in the form of workshop activities attended by the local Jatiwangsan Village community. This activity workshop "(Creative Economy) Implementation of Community Economic Improvement Through Garbage Bank Activities". 28 members of the PKK participated in this activity. The PKM activity was divided into three stages, namely the Socialization, Monitoring and Evaluation stages. The material provided was related to "Community-Based Waste Management". In carrying out this activity the Jatiwangsan PKK member community group was very enthusiastic when participating in this activity, this can be seen from the desire of the community members to provide further assistance in implementing the waste bank program. The results of the workshop activities showed that the percentage of understanding of the PKM participants, as much as more than 80% of the participants really understood the material related to "Community-Based Waste Management". In this case PKK members already understood how to manage and sort waste. As for the Garbage Bank materials, more than 75% of the participants understood the forms of waste management and sorting. The method used in the implementation of this workshop activity is a quantitative approach. The purpose of implementing this activity is waste management and economic improvement.